2015
DOI: 10.1002/hed.24335
|View full text |Cite
|
Sign up to set email alerts
|

Features and prognostic utility of biopsy in oral squamous cell carcinoma

Abstract: A future clinical trial will compare the routine biopsy technique with standardized deeper biopsy techniques using punch biopsy to sample invasive fronts and investigate opportunities for up-front staging using a combination of histological features and epithelial and stromal molecular biomarkers in OSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1857-E1862, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…It has been demonstrated that the mean biopsy depth of 4.1 mm is greater than the corresponding true tumor depth determined from the resection margin in 28% of OSCC cases. 11 This finding has some prognostic value, considering that 18% of the biopsies reported a tumor depth >4 mm, an important cutoff associated with more aggressive disease. 12 Therefore, a tumor depth of >4 mm in small lesions, such as T1 or early T2 tumors, could influence the decision on the optimum treatment to utilize.…”
Section: Dear Editormentioning
confidence: 89%
See 1 more Smart Citation
“…It has been demonstrated that the mean biopsy depth of 4.1 mm is greater than the corresponding true tumor depth determined from the resection margin in 28% of OSCC cases. 11 This finding has some prognostic value, considering that 18% of the biopsies reported a tumor depth >4 mm, an important cutoff associated with more aggressive disease. 12 Therefore, a tumor depth of >4 mm in small lesions, such as T1 or early T2 tumors, could influence the decision on the optimum treatment to utilize.…”
Section: Dear Editormentioning
confidence: 89%
“…12 Therefore, a tumor depth of >4 mm in small lesions, such as T1 or early T2 tumors, could influence the decision on the optimum treatment to utilize. 11 In the Discussion section, it has been reported, with regard to PVL lesions, that ". .…”
Section: Dear Editormentioning
confidence: 99%
“…The primary role of OSCC biopsy is diagnostic but recently, there is increasing advocacy for a prognostic role for it [3,4,16,17]. Only optimal (at least > 5 mm deep) biopsies can serve this role.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer diagnosis is mandatorily followed by preoperative staging (usually by clinical and imaging modalities) in order to determine the risk category and the most appropriate treatment plan for the patient. The need for extending the role of the biopsy from being only diagnostic to also include prognostication has recently been highlighted by some investigators [3,4]. In OSCC (and OTSCC), tumor grade of differentiation has not been found to be particularly useful in prognostication despite being the only universal routinely assessed histological feature in preoperative biopsies by pathologists [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation